Chapter Introduction - Burke, Danita Catherine (Taylor & Francis, 2023)
This book posits that the normalization and devaluation of experiences of violence and trauma against certain cultural groups involved in the sealing debate, while framing others as deserving of some exception, has created a gray area for cultural violence to occur, and Newfoundlanders and Labradorians have fallen into this grey area. The introduction also argues that the dehumanization of commercial seal hunters, especially non-Indigenous, as cruel immoral killers while casting Indigenous hunters as acceptable traditionalists provided that they only adhere to a strict externally imposed understanding of subsistence/personal use hunting is undermining Inuit/Indigenous economies and their sealing advocates who to argue that the European Union commercial seal product import ban should end.